Falsehood and False Prophets in Jeremiah: A View on LXX-Jer and P-Jer - Koralija, Srećko (Vetus Testamentum, 2025)
This article explores the use of שֶׁקֶר in MT-Jer, and the manner in which the Septuagint (LXX) and Peshitta (P) read it. In that regard, the article also discusses lying, falsehoods (ψευδής, ψεῦδος, ἄδικος, µάτη, ܫܘܩܪܐ, ܕܓܠܘܬܐ), and false prophets (ψευδοπροφήτης, ܢܒܝܐ ܕܓܠܐ) in LXX and P. As such, it pioneers the examination of P-Jer’s perspective on false prophets. The article demonstrates that the translators of LXX and P approached the Hebrew source text in a manner that was not strictly literal, aligning with the nuances of the target language. It is argued that both LXX-Jer and P-Jer illuminate the polysemy inherent in the Hebrew lexeme שֶׁקֶר. In addition, both versions demonstrate a degree of textual liberty and interpretative renderings. Finally, the article demonstrates that unlike LXX, which labels Hananiah as a false prophet only once (LXX-Jer 35:1), P systematically designates him so throughout P-Jer 28. Consequently, the article also adds weight to the argument opposing a direct textual influence of LXX on P.